FTO alleviated the diabetic nephropathy progression by regulating the N6-methyladenosine levels of DACT1 - Li Xuanwen; Huang Qing; Gu Shinong; Zheng Ping (Open Life Sciences)
FTO-medicated m6A modification of DACT1 was dependent on IGF2BP1 in DN progression.